ISOLATION OF ESCHERICHIA COLI FROM PREGNANT WOMEN’S URINE AT BINANGA HEALTH CENTER MAMUJU - Mahmud, Abbas; Haninggar, Rizki Dyah; Ahmady, Ahmady (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2025)
Background: Urinary tract infections (UTIs) and asymptomatic bacteriuria during pregnancy can have detrimental effects on both maternal and fetal health. These conditions are associated with complications such as acute maternal illness, low birth weight, preeclampsia, preterm delivery, and intrauterine growth restriction. The causative agents of UTIs are Escherichia coli, Klebsiella sp, and Staphylococcus spp.Objective: to isolate and identify E. coli in the urine samples of pregnant womenMethods: This study employed a descriptive observational design. The research sample included pregnant women attending the Binanga Community Health Center in Mamuju. Urine was cultured in BHIB and incubated at 37°C for 24 hours. Subsequent bacterial isolation was performed by subculturing onto EMBA media and MacConkey agar. Colonies that developed were then analyzed using Gram staining and examined microscopically.Results: Of 25 sample urine samples from pregnant women, 25 were culture-positive on MacConkey Media and EMBA Media. 14 (56%) isolate colored bacteria metallic green on EMBA media that EMBA media is specifically for the growth for E. coli bacteriaConclusions: 56% of the bacterial isolates from the urine samples of pregnant women were indicated as Escherichia coli, based on the presence of metallic green colonies observed on EMBA media